Pengaruh Kode Etik Profesi Polri dan Disiplin Kerja Anggota Polri Terhadap Komitmen Organisasi di Lingkungan Polres Sumedang - Syaifuddin Syaifuddin (STIE AMKOP, 2023)
The purpose and core problem in this study is to determine the effect of the Police Professional Code of Ethics and Discipline of Police Members on Organizational Commitment in the Sumedang District Police Environment. The method used in this research is quantitative research methodology. Data collection techniques with questionnaires and observation techniques. The population in this study was 1146. The sampling technique used was propotionate stratifield ramdon sampling. The sample size was 296 respondents. The results of the study prove that the Police Professional Code of Ethics (X1) as measured by Organizational Commitment (Y) has a positive and significant contribution to the high and low organizational commitment of 36.8%, the Work Discipline of Police Members (X2) as measured by Organizational Commitment (Y) has a positive and significant contribution to the high and low organizational commitment of 64.6%. Simultaneously, the Police Professional Code of Ethics (X1) and Work Discipline of Police Members (X2) contributed positively and significantly to Organizational Commitment (Y) by 91.3%. The remaining 8.7% is the influence that comes from other factors. The conclusion of this study is that the Police Professional Code of Ethics and Work Discipline of Police Members affect the Organizational Commitment of the Police in the Sumedang District Police. Suggestions from this study are that in an effort to increase the organizational commitment of the Police, physical and mental coaching, psychological coaching and counseling, and guidance on narcotics by the National Narcotics Agency should be carried out, eliminating discriminatory Polri task practices, increasing community participation in overseeing the implementation of Polri duties, increasing human resource capabilities through improving the quality of investigators, increasing awareness and compliance of Polri members, procuring and managing task support facilities, and building public understanding of the main duties and functions of Police Members. Keywords: Police Professional Code of Ethics, Work Discipline of Police Members, Organizational Commitment.